2018
DOI: 10.1007/s13744-018-0590-y
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of α-Amylase from Midgut of Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae) Larvae

Abstract: The lesser mealworm, Alphitobius diaperinus (Panzer), is the main insect pest in the poultry industry, thus causing serious damage to production. In this work, the properties of midgut α-amylase from larvae of A. diaperinus were characterized, and its in vitro activity to proteinaceous preparations from different cultivars of common bean (Phaseolus vulgaris) was determined, as well as the amylolitic activity of insects reared on different types of poultry diet. In order to establish some assay conditions, time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…In lesser mealworm, a 42-kDa α-amylase showed optimal activity at 45 C and pH 5.0. Moreover, previous results showed that the activity of α-amylase in lesser mealworm can be significantly inhibited by some proteinaceous extracts from bean cultivars (Cruz et al, 2018). The structure of α-amylase (CcAmy) in Callosobruchus chinensis was shown to be different from TcAmy in Tribolium castaneum, although they both belong to Coleoptera (Channale et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In lesser mealworm, a 42-kDa α-amylase showed optimal activity at 45 C and pH 5.0. Moreover, previous results showed that the activity of α-amylase in lesser mealworm can be significantly inhibited by some proteinaceous extracts from bean cultivars (Cruz et al, 2018). The structure of α-amylase (CcAmy) in Callosobruchus chinensis was shown to be different from TcAmy in Tribolium castaneum, although they both belong to Coleoptera (Channale et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Domain B contains several α-helices and β-folded chains that are important components of the active site, whereas domain C is formed by antiparallel β-sheets that are thought to protect the stability of hydrophobic amino acids in the catalytic centre (MacGregor et al, 2001). Since digestive enzymes exhibit potential use as molecular targets for pest control, α-amylases are widely studied in different insects (Ashouri & Farshbaf Pourabad, 2020;Celinska et al, 2015;Channale et al, 2016;Cruz et al, 2018). In lesser mealworm, a 42-kDa α-amylase showed optimal activity at 45 C and pH 5.0.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperature for maintaining α-amylase activity in insects is between 30 • C and 60 • C, and α-amylase activity drops sharply when the temperature reaches above 60 • C. A study showed that α-amylase from the midgut of Alphitobius diaperinus (Coleoptera: Tenebrionidae) larvae reached an optimal temperature of 45 • C. It maintained 34.6% activity after being kept at 60 • C for 5 min, and activity dramatically decreased to 23% when placed at 80 • C for 1 h. The presence of high levels of Ca 2+ (2 mM) and Na + (100 mM) ions was also shown to decrease enzyme activity [47]. The H. armigera α-amylase optimum temperature is 50 • C [43].…”
Section: Properties Of Insect α-Amylasesmentioning
confidence: 99%
“…A. diaperinus pierwotnie pochodzi z rejonów tropikalnych Afryki (10,39). Owad popularnie występuje w kurnikach (7,17,31,37,47) zwłaszcza, gdy kurczęta utrzymywane są na ściółce (20,36). Wysoka temperatura powietrza podczas odchowu kurcząt, zaleganie pomiotu kurzego, wysoka wilgotność względna powietrza oraz wilgotna ściółka -są to czynniki, które stwarzają korzystne warunki do rozwoju chrząszczy przez cały rok (4).…”
Section: Artykuł Przeglądowy Reviewunclassified